Tameness of joins involving the pseudovariety of local semilattices - Costa, José Carlos (2012)
In this paper we prove that, if V is a kappa-tame pseudovariety which satisfies the pseudoidentity xy^{ω+1}z=xyz, then the pseudovariety join LSl v V is also kappa-tame. Here, LSl denotes the pseudovariety of local semilattices and kappa denotes the implicit signature consisting of the multiplication and the (omega-1)-power. As a consequence, we deduce that LSl v V is decidable. In particular the joins LSl v Ab, LSl v G, LSl v OCR and LSl v CR are decidable.